In Search of Republican Unity: Excluding Political Opponents from the Vote during the Dutch Revolution (1780-1800) - Rutjes, Mart (Early Modern Low Countries, 2022)
The importance of the Dutch Revolution of the late eighteenth century for political developments in the Northern Netherlands is still contested. Most historians view the period as the starting point of a number of democratic institutions, including elections. Others have pointed out, however, that the nineteenth century shows a remarkable amount of continuity in political practice with the early modern period, and have therefore questioned the impact of political change. Scholarship on the political system during the revolutionary era has paid little attention to the exclusion of a specific group from electoral politics: political opponents of the revolution. The debates on the question of whether Orangists should have access to the ballot were intense in the Northern Netherlands, where a political struggle between Patriots and Orangists had been taking place since the 1780s. Through a consideration of why the Dutch revolutionaries placed such electoral barriers against their political adversaries (mainly Orangists, but for a brief period also moderates and federalists), this essay argues that this period ought to be viewed with its particular revolutionary character in mind, rather than considering it simply as a period that relied on old practices or one that gave birth to new ones.